The utility of endobronchial ultrasound-transbronchial needle aspiration in patients with suspected extra-pulmonary sarcoidosis without thoracic lymphadenopathy. (September 2020) - Aravena, Carlos; Almeida, Francisco A.; Culver, Daniel A.; Ribeiro Neto, Manuel L.
Abstract: Background: Diagnosis of extra-pulmonary sarcoidosis can be difficult, and a biopsy is usually required. We evaluated the utility of endobronchial ultrasound-transbronchial needle aspiration (EBUS-TBNA) in patients with suspected extra-pulmonary sarcoidosis with thoracic lymph nodes ≤10 mm on chest computed tomography (CT) and no or minimal pulmonary infiltrates. Methods: The Cleveland Clinic bronchoscopy registry was screened. Patients with thoracic lymph nodes >10 mm on short axis or significant pulmonary infiltrates in the chest CT scan were excluded. Two separate analyses using expert consensus (before and after release of bronchoscopy results) were the reference standard. Results: 15 patients met the inclusion criteria. 40% had suspected ocular, 33% cardiac and 27% neurologic sarcoidosis. Six patients (40%) had EBUS-TBNA compatible with sarcoidosis. When the reference standard was the consensus diagnosis blinded to bronchoscopy results, the sensitivity, specificity, positive predictive value and negative predictive value of EBUS-TBNA were 56%, 83%, 83%, and 56% respectively. The combination of a positive EBUS-TBNA and BAL CD4/CD8 improved the specificity from 83 to 100%, but the difference was not statistically significant (p = 0.074). When the reference standard was the consensus diagnosis with the bronchoscopic results, the sensitivity, specificity, positive predictive value and negative predictive value of EBUS-TBNA were 75%, 100%, 100%, and 78% respectively. Conclusions: In patients with suspected extra-pulmonary sarcoidosis, the EBUS-TBNA may be useful in the diagnosis of patients with thoracic lymph nodes ≤10 mm and no or minimal pulmonary infiltrates on chest CT. Larger and prospective studies are needed to validate our findings.